PENGARUH MEDIA VIDEO PEMBELAJARAN DAN PERAN GURU TERHADAP HASIL BELAJAR MATEMATIKA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING ( STUDY KASUS PADA SISWA KELAS VI SD GUGUS 1 KECAMATAN BINUANG ) - Lily Norma Yanti Lily (JURNAL KINDAI, 2022)
Based on the initial data information obtained, the results of the recapitulation of the average PTS grades in semester 1 of class VI students in Cluster 1, Binuang District in the last 3 years have decreased.This study aims to determine the direct and indirect effect of instructional video media, the role of the teacher on mathematics learning outcomes with motivation as an intervening variable.This research is an ex post facto research with a quantitative approach. The population in this study were all sixth grade elementary school students in Cluster 1, Binuang District. The sample in this study there were 60 people with purposive sampling technique. Data tested with Smart PLS version 3.0The results of this study indicate that; 1) learning video media has no significant effect on motivation 2) The role of teachers has a significant effect on motivation 3) learning video media has a significant effect on learning outcomes 4) the teacher's role has no significant effect on learning outcomes 5) motivation has a significant effect on learning outcomes 6) video media learning does not have a significant effect on learning outcomes in mathematics with motivation as an intervening variable. 7) The role of teachers has a significant effect on learning outcomes in mathematics with motivation as an intervening variable in class VI SD Gugus 1, Binuang District.